VD_FINDINFO Faillite / 2010 / 25 vom 29. April 2010 - VD Tribunal cantonal (2010)
DÉPENS, RÈGLEMENT AMIABLE DES DETTES | 102 al. 2 CO, 69 al. 2 ch. 1 LP, 82 LP, 7 al. 2 LPAg, 38 al. 3 LVLP, 55 OELP, 56 al. 2 OELP